What outcome measures are commonly used for Complex Regional Pain Syndrome clinical trials? A systematic review of the literature. (15th June 2015) - Grieve, S.; Jones, L.; Walsh, N.; McCabe, C.
Abstract: Background and objective: Complex Regional Pain Syndrome (CRPS) is a chronic pain condition, often triggered by trauma to a limb and characterized by sensory, motor, autonomic and trophic changes within the affected limb. Due to the multi‐faceted nature of the condition there are a wide range of potential health outcome measures for use within CRPS related clinical trials. This aim of this systematic literature review was to identify which patient or health professional questionnaire format outcome measures have been used in CRPS specific clinical trials, and which of these have been developed specifically for use in CRPS populations. Information gained from this review will inform an international consortium project to define a Core Outcome measurement set for CRPS Clinical trials. Databases and data treatment: The electronic databases EMBASE, Medline, PsycInfo, CINAHL and LILACS were systematically searched from January 2000 until April 2014. Results: One hundred and four full text papers were obtained with 68 questionnaire outcome measures identified. Five of these outcome measures were validated for CRPS. Of those outcome measures used since 2000, those addressing physical functioning were most prevalent. Conclusions: Currently, CRPS clinical trials use a wide range of outcome measures making the potential to synthesize evidence problematic. There is no internationally agreed core measurement set. This diversity of outcome measures demonstrates a clear need for the development of a core measurement set to be used in CRPS clinical trials.